Design and Development Performance Assessment System for Medical Staff Implementing the Regulations of the Indonesian Ministry of Health (Case Study: Arifin Achmad General Hospital, Riau Province) - Teddie Darmizal (Engineering And Technology Journal, 2024)
The difficulty in conducting performance assessments of medical staff is the background for the Arifin Achmad Regional General Hospital (RSUD) to implement performance assessment standardization which refers to the technical guidelines for the assessment of Individual Work Indicators (IKI), Minimum Service Standards (SPM) of Hospitals, and the Dictionary of Performance Indicators of Hospitals and Centers (KIKRSB). The standardization of the assessment will be implemented in the Information System so that it can facilitate the process of input and monitoring of the performance results of the assessed medical staff. Each indicator is weighted with urgency, seriousness and growth (ultrasound) techniques. The Medical Staff Performance Assessment Information System was built using PHP programming language, tested with the user acceptance test (UAT) technique to the deputy director of medical and nursing and related medical staff at Arifin Achmad Hospital with a result of 95.4% indicating that the system was acceptable.